Pandangan Masyarakat Kolaka Utara Tentang Peran Mangrove sebagai Penyerap Carbon (Blue carbon) dalam Memitigasi Perubahan Iklim - Hamid, Nisrina; Eliyanti Agus Mokodompit, Eliyanti (LP3M, Universitas Muhammadiyah Kendari, 2025)
This study examines the perceptions of the community in North Kolaka regarding blue carbon mangroves in the context of climate change mitigation. Using a descriptive qualitative approach, the research involved 200 respondents from two districts: Pakue and Watunohu. The results indicate that the majority of respondents have a high awareness of the importance of mangroves as carbon sinks and environmental protection. However, understanding of the blue carbon concept remains low, with 37.5% of respondents indicating they have a fair understanding. Furthermore, 88 % of respondents believe that mangroves play a crucial role in climate change mitigation. This study recommends more intensive educational programs to enhance knowledge and community involvement in sustainable mangrove management, in order to support efforts for mitigation and the preservation of mangrove ecosystems in North Kolaka Regency.